2013
DOI: 10.1111/febs.12616
|View full text |Cite
|
Sign up to set email alerts
|

The degradation (by distinct pathways) of human d‐amino acid oxidase and its interacting partner pLG72 – two key proteins in d‐serine catabolism in the brain

Abstract: Human D-amino acid oxidase (EC 1.4.3.3; hDAAO) is a peroxisomal flavoenzyme significantly enriched in the mammalian brain. hDAAO has been proposed to play (with serine racemase; EC 5.1.1.18) an essential role in the catabolism of D-serine, an 'atypical' key signalling molecule that acts as allosteric activator of the N-methyl-D-aspartate-type glutamate receptor (NMDAr). hDAAO and its interacting partner pLG72 have been related to schizophrenia, a highly disabling psychiatric disorder in which a dysfunction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 60 publications
(134 reference statements)
4
47
1
Order By: Relevance
“…Co-staining with antibodies against mono-and polyubiquitylated conjugates indicated that cytosolic and nuclear protein accumulations are positive for ubiquitin (data not shown). This is in line with the fact that hDAAO was shown to be ubiquitylated in glioblastoma cells (Cappelletti et al 2013). Concurrent manipulative in vitro experiments also demonstrated that proteasomal inhibition resulted in a comparable cytosolic and nuclear accumulation of DAAO (Luks et al, unpublished data).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Co-staining with antibodies against mono-and polyubiquitylated conjugates indicated that cytosolic and nuclear protein accumulations are positive for ubiquitin (data not shown). This is in line with the fact that hDAAO was shown to be ubiquitylated in glioblastoma cells (Cappelletti et al 2013). Concurrent manipulative in vitro experiments also demonstrated that proteasomal inhibition resulted in a comparable cytosolic and nuclear accumulation of DAAO (Luks et al, unpublished data).…”
Section: Discussionsupporting
confidence: 54%
“…However, both DAAO and α2u-globulin inherently have a long half-life (hDAAO: approx. 60 h (Cappelletti et al 2013);α2u-globulin: approx. 6 h (Lehman-McKeeman et al 1990)), whereby binding of chemicals to α2u-globulin extends this half-life markedly and exacerbates the accumulation of α2u-globulin in the lysosomes of exposed male rats (Swenberg et al 1989;Lehman-McKeeman et al 1990;Frazier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…the enzyme that degrades the neuromodulator D-serine in vivo [18]. The standard assay for glycine requires the derivatization of the amino acid followed by separation (and quantification) by means of HPLC on a C8 column, each run requiring 60 min.…”
Section: Glycine and Sarcosine Detectionmentioning
confidence: 99%
“…Cellular amino acids were extracted as described previously [18]: 2.5 9 10 5 U87 cells were resuspended in 1 mL of ice-cold 5% trichloroacetic acid, sonicated and centrifuged for 45 min at 16 000 g. For the HPLC assay, the soluble fraction was extracted with water-saturated ether, neutralized and derivatized with o-phthaldialdehyde/N-acetyl-L-cysteine. Glycine was resolved by HPLC chromatography on a 5-lm Waters C8 reversed-phase column (Waters Corp., Milford, MA, USA) eluted under isocratic conditions (100 mM sodium acetate buffer, pH 6.2, 1% tetrahydrofuran at 1 mLÁmin À1 ; 60 min per run).…”
Section: Glycine/sarcosine Detection In Biological Samplesmentioning
confidence: 99%
See 1 more Smart Citation